The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2215/cjn.04610908
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Adults Who Undergo Transplantation with Single Pediatric Kidneys

Abstract: Background and objectives: The optimal donor age for transplanting a single pediatric kidney in an adult recipient remains unknown. En block kidney transplantation is usually performed when the donor age is <5 yr.Design, setting, participants, & measurements: We compared the outcomes of adult patients who underwent transplantation with single pediatric kidneys from donors who were younger than 5 yr (group 1, n ‫؍‬ 40) and from donors who were aged 5 to 10 yr of age (group 2, n ‫؍‬ 39) in our center.Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 18 publications
(22 reference statements)
1
26
0
Order By: Relevance
“…Balamuthusamy et al [12] described that obesity was not a negative prognostic factor. Zhang et al [14] observed similar outcome in adult recipients of grafts from donors less than 5 years and recipients of grafts from older PDK, aged 5-10 years.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Balamuthusamy et al [12] described that obesity was not a negative prognostic factor. Zhang et al [14] observed similar outcome in adult recipients of grafts from donors less than 5 years and recipients of grafts from older PDK, aged 5-10 years.…”
Section: Discussionmentioning
confidence: 82%
“…Clinical findings and outcome of these 99 patients have been described in detail in several publications [11][12][13][14]. Conversely, the present study is a thorough review of the renal biopsies, to investigate findings in adult recipients of PDK grafts, and compare the pathology with bx of ADK grafts.…”
Section: Patient Datamentioning
confidence: 95%
“…There have been recent reports of excellent 5-year kidney graft outcomes using pediatric donors to adult recipients, with one study showing a small effect on graft survival when comparing kidneys transplanted to adults from donors weighing 20 to 60 kg versus 10 to 19 kg and a greater effect from donors weighing 5 to 9 kg (21,22). The potential for enhanced glomerular functional reserve in pediatric kidneys clouds comparisons between pediatric donors and adult donors, and for this reason, our study specifically excluded pediatric donors and en bloc dual kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of vascular complications (i.e., renal vein thrombosis, renal artery thrombosis) is higher when these kidneys are transplanted singly than as en bloc. 28 This may be minimized by concentrating the experience in selected centers initially until considerable experience is built up in this area. The results from our study show that the grafts from younger than 5 years donors was comparable to those 5 years or older to younger than 18 years, which is evident in not only the high rates of immediate graft function but also excellent graft and patient survival and 1 year graft function.…”
Section: Discussionmentioning
confidence: 99%